ANALISIS TINGKAT DAN FAKTOR PENYEBAB KERAWANAN BANJIR DI KECAMATAN SIBERUT SELATAN - Ipan Karasius; Desi Eka Putri; Heny Mariati; Febrianto, Hary; Hary, Hary Febrianto (Universitas Prof. Dr. Hazairin, S.H, 2024)
This study aims to (1) analyze the distribution of flood vulnerability levels in South Siberut District, and (2) analyze the dominant factors causing flood vulnerability in South Siberut District. The sample of this study is some floodprone areas in South Siberut District. The research method used is quantitative descriptive. Data processing to determine the distribution of flood vulnerability levels is carried out by overlaying, scoring, and weighting from slope data, elevation, rainfall, soil type, river distance, and land use. To determine the dominant factor causing flooding using the Pearson correlation test. Based on the results of the study, it can be concluded that the level of flood vulnerability in South Siberut District is divided into three classes, namely the low vulnerability level covering an area of 34,991.67 ha (71.86%), the medium vulnerability level covering an area of 12,488.61 ha (25.65%), the high vulnerability level covering an area of 1,215.30 ha (2.50%). The rainfall parameter is the dominant factor causing flooding in South Siberut District because the correlation results get the highest value of 0.693, followed by land use of 0.503, elevation of 0.313, river distance of 0.281, soil type of 0.134, and slope of 0.126.